(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
China has grown fast in recent decades and its context is poorly understood in the West. Thus, the way that the government acts in the country’s scientific, technological and innovative oriented growth deserves attention, especially from emerging countries. Therefore, the present study aims to analyze the role of the government in Chinese science and technology parks. To this end, a literature review was performed in the Scopus database and 12 articles were filtered. The findings demonstrate that the Chines e government has a strong influence on the development of parks in the country. Since 1980, it has strongly promoted policies for the creation of technology parks, mainly through the Torch Program. Currently, this innovation oriented policy is studied by s everal authors who pursuit a better understanding of the Chinese innovation system.